Utilizing Cognitive Processing Therapy to Treat Sexual Trauma with a Pakistani-American: A Case Report. (December 2021) - Glowacki, Christopher R.; Glowacki, Zachary R.
There is a paucity of research of traditional psychotherapy approaches with individuals of South Asian descent, specifically Pakistani-Americans. In particular, there are very few cases in existing literature highlighting the effectiveness of Cognitive Processing Therapy (CPT) with Pakistani-Americans who have experienced sexual abuse. Due to cultural values, individuals of South Asian descent are less likely to pursue traditional psychotherapy and even far less likely to complete and/or benefit from it. The current case study focused on depression and trauma-related symptoms (e.g., guilt, shame, embarrassment) in the context of repeated sexual abuse for over 20 years. The PTSD Checklist (PCL-5) and Patient Health Questionnaire (PHQ-9) confirmed qualitative reports and therapist observations of improvement. This case suggests a westernized and protocol-driven treatment can be a viable intervention for individuals of SA descent with a history of sexual trauma. A strong therapeutic relationship and open discussion of diversity considerations were necessary for this treatment to work. This case reflects potential support for CPT as a treatment utilized across cultures for trauma-related symptoms.